Morphological, pathogenic and genetic variability in castor wilt isolates - M. SUJATHA; MA RAOOF, M. SANTHA LAKSHMI PRASAD* (Indian Phytopathology, 2008)
Castor wilt caused by Fusarium oxysporum t.sp. ricini is an economically important and major disease of castor. Variation in resistance to wilt was observed among castor hybrids! varieties in different cultivated areas because of pathotypes. Isolates of fungus were collected from different castor growing areas of India and morphological, cultural characters were studied. The effect of culture filtrates of these isolates was tested on germination of castor seeds and wilt incidence with a view to study differences in the toxin production among the isolates. The isolates showed variation in mycelial growth, pigmentation, sporulation, size of conidia and production of micro and macroconidia. Culture filtrate of the isolates reduced the germination of castor seeds. The germination was directly correlated with the concentration of the culture filtrate in comparison to check. Maximum inhibition in germination was observed with undiluted culture filtrate followed by 100 and 75 ppm concentration. The isolates also differed in the degree of inhibiting the root growth. All the seedlings wilted in undiluted culture filtrate of all isolates whereas, no wilting was observed in seedlings kept at 25 ppm conc. Isolates varied in production of toxin and thereby wilt incidence. The reaction of the 29 isolates on castor cultivars indicated the existence of different virulence of isolates in different castor growing areas of country and five pathotypes of the pathogen were characterized. Isolates 2,14 and 15 were virulent and attacked DCS 9 and Kranthi cultivars. The genetic variation of isolates of F. oxysporum t.sp. ricini was studied by random amplified polymorphic DNA analysis. Tho isolates were grouped into five clusters based on molecular polymorphism generated by RAPD primers. The grouping of isolates based on pathogenic variation has no correlation with grouping based on RAPD analysis with most of the test isolates.